2009
DOI: 10.1007/s10344-009-0335-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fire and cattle grazing on amphibians and lizards in northeastern Argentina (Humid Chaco)

Abstract: Richness, diversity and abundance of amphibians and lizards were compared in four sites subjected to different fire and grazing regimes in Mburucuyá National Park (Corrientes, Argentina). The surveys were performed using drift fence-pitfall traps randomly distributed in four sites subjected to the following prescribed fire and grazing regimes: (A) no fire or grazing for the last 12 years (control), (B) 3 years since the last prescribed fire, (C) annual prescribed fire and (D) annual prescribed fire and grazing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 35 publications
2
17
2
2
Order By: Relevance
“…Our results agree with those of Perry et al (2012), who found greater abundance of toads after a short-rotation controlled burning in forests, and suggest that burning can also benefit toads in marshes. Our findings, however, differ from the results of a similar study conducted in grasslands in northern Argentina, which found that prescribed burning, combined with intensive grazing, had large negative effects on amphibians (Cano and Leynaud 2009). Likely explanations for these differences are that burning may cause considerably more direct damage to amphibians in grasslands than in wet marshes and that grazing in our study was implemented at a low intensity and in wet habitats, which may better tolerate grazing than grasslands.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Our results agree with those of Perry et al (2012), who found greater abundance of toads after a short-rotation controlled burning in forests, and suggest that burning can also benefit toads in marshes. Our findings, however, differ from the results of a similar study conducted in grasslands in northern Argentina, which found that prescribed burning, combined with intensive grazing, had large negative effects on amphibians (Cano and Leynaud 2009). Likely explanations for these differences are that burning may cause considerably more direct damage to amphibians in grasslands than in wet marshes and that grazing in our study was implemented at a low intensity and in wet habitats, which may better tolerate grazing than grasslands.…”
Section: Discussioncontrasting
confidence: 57%
“…However, these studies were conducted in forest and grassland ponds and we know little about the separate or combined effects of grazing and fire management on amphibians in marshes and reedbeds. The combined effects of grazing and burning have been studied only in grasslands of northern Argentina (Cano and Leynaud 2009). All other studies of wetlands followed only one management action and focused on plants or invertebrates (Ausden et al 2005;Ditlhogo et al 1992;Hardman et al 2012;Schmidt et al 2005), likely because the restored/managed areas were too small (under 1 hectare) to evaluate the impacts of disturbance on taxonomic groups such as vertebrates (Wagner et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The few reported results indicate mainly negative indirect effects of livestock on amphibians (Maxell 2000;Jansen and Healey 2003;Cano and Leynaud 2010), such as changes in water pH (Boschi and Baur 2006). It is well known that amphibians are susceptible to pH changes, since water acidification has a negative effect on species diversity and density (Wyman and Jancola 1992), reducing oviposition rate and larval growth and viability (Freda and Dunson 1986;Freda et al 1991;Vertucci and Stepen 1996).…”
Section: Introductionmentioning
confidence: 95%
“…Group planting uses larger seedlings or saplings (0.8-1.5 m tall) and a wider initial spacing (1 × 1 m). In group planting, both the total number of saplings per group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and the number of additional, shade-tolerant trainer tree saplings per group are designed. Trainer trees are commonly planted on the perimeter of groups to control ground vegetation and to shade oak stems, thus preventing development of epicormic sprouts.…”
Section: Long-term Restorationmentioning
confidence: 99%
“…Forest fires can also decrease the income of farmers [4,18,20]. Forest fires can change the habitat quality for wildlife by altering the abundance, distribution, productivity, and diversity of the animals occupying these habitats [21][22][23][24]. Many animals often require more than one type of habitat due to their different requirements for each stage of their life cycles.…”
Section: Introductionmentioning
confidence: 99%